Enhancing Children's Spiritual and Cognitive Development Through a Hadith Memorization Guide for Teachers and Parents - Sari, Aida Rika; Arifin, Imron; Pramono, Pramono (Muallimun : Jurnal Kajian Pendidikan dan Keguruan, 2026)
This study examines a collaborative hadith memorization model involving teachers and parents to enhance children’s spiritual and cognitive development in early childhood education. A qualitative case study was conducted at RA Persis Bangil, Indonesia, involving one classroom teacher and ten parents as participants, with thirty one students observed. Data were collected through in depth interviews, observations, and focus group discussions and analyzed using thematic analysis. The findings reveal that interactive memorization methods, including pop up books, storytelling, and game based media, improved children’s engagement and retention. Teacher parent collaboration strengthened the internalization of spiritual values and ensured learning continuity between school and home. Supportive physical and emotional environments further accelerated moral habituation and cognitive comprehension. The study proposes a holistic religious learning framework integrating pedagogical innovation, family engagement, and environmental support to optimize early childhood development.